The Dead Words of Minangkabaunese Found in Pasir Talang-Solok Selatan - Chyntia Mayelnic; Jufrizal Jufrizal (English Language and Literature, 2022)
This article discusses Minangkabaunese language, especially dead words that occur in Pasir Talang, Solok Selatan, West Sumatra. There are many dead words or words that Pasir Talang society has forgotten. Language death can occur due to no longer utilized terms or dead words that occur on a daily. The purpose of this study was to find dead words in Pasir Talang-Solok Selatan. This research belonged to the descriptive qualitative approach in which the elaboration of data is presented in the form of explanations and groupings of data. The data source of this research is the dead words in Pasir Talang-Solok Selatan. Based on the result of the research, the researcher found 69 dead words out of a total of 179 words. There were four lexical classes of words found from 69 dead words, which are nouns, verbs, adjectives, and adverbs. The noun (72,5%) is the most emerging with various variations. This happened because the object was no longer found in existence, besides that the object was replaced with a more practical and modern item.